The narrative of a sanctuary : a didactic design approach for the cultural and biophysical heritage of Wonderboom fort and Nature Reserve, Pretoria, South Africa - Breed, Ida (University of Pretoria, 2013)
Dissertation (ML(Prof))--University of Pretoria, 2011.